Extracellular vesicles from blood of breast cancer women induce angiogenic processes in HUVECs. (June 2022) - Garcia-Hernandez, Alejandra; Reyes-Uribe, Emmanuel; Arce-Salinas, Claudia; de la Cruz-Lopez, Karen-Griselda; Manzo-Merino, Joaquin; Guzman-Ortiz, Ana-Laura; Quezada, Hector; Cortes-Reynosa, Pedro; Breton-Mora, Fernando; Elizalde-Acosta, Irma; Thompson-Bonilla, Rocio; Salazar, Eduardo Perez
Abstract: Breast cancer is the most frequent malignancy among women in developed countries and the main cause of death related to cancer in women worldwide. Extracellular vesicles (EVs) are vesicles with a variable size enclosed within a phospholipid bilayer that contain a variety of molecules with biological activity. Cancer cells release EVs that induce proliferation, escape from apoptosis, reprogramming energy metabolism, invasion and metastasis. In this study we studied whether EV fractions deprived of platelet EVs from breast cancer women (BC EVs) can mediate cell processes related with angiogenesis in human umbilical vein endothelial cells (HUVECs). Our findings demonstrate that BC EVs enhance migration, invasion and formation of new tubules in HUVECs, compared with EV fractions deprived of platelet EVs from healthy women (Ctrl EVs). In summary, we demonstrate, for the first time, that BC EVs induce cellular processes in HUVECs that participate in angiogenesis. Graphical Abstract: ga1 Highlights: Extracellular vesicles from breast cancer women mediate angiogenesis. Extracellular vesicles from breast cancer women mediate migration in HUVECs. Extracellular vesicles from breast cancer women mediate invasion in HUVECs.